THE ESSENCE AND SPECIFICITY OF INNOVATIVE TOURISM ACTIVITY - Nishanova Xafiza Vafokulovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the key areas of innovation in the tourist industry, as well as the variables that influence tourism’s inventive development. Specific aspects of the tourist product, producers and users of tourism services, according to the author, are among the criteria that influence the characteristics of creative activity in the tourism industry.